18F-Fluorothymidine PET for Functional Response Assessment Following Radiation Therapy for Extramedullary Hematopoiesis. (September 2021) - Campbell, Belinda A.; Callahan, Jason; Cole-Sinclair, Merrole; MacManus, Michael; Hofman, Michael S.
Abstract : Abstract: As a marker of cellular proliferation, 18 F-fluorothymidine (FLT) PET can detect the distribution of proliferating hematopoiesis and has an emerging role in the investigation of hematopoietic disorders. These images demonstrate the novel utility of 18 F-FLT PET for imaging sites of extramedullary hematopoiesis (EMH) in a patient with Chuvash-type polycythemia and suggest a role for 18 F-FLT PET in response assessment following radiotherapy. Further, the discordant response observed in the irradiated marrow and sites of EMH is a unique discovery, possibly suggesting the influence of the microenvironment favoring more rapid recovery of proliferative function within EMH sites.